2016
DOI: 10.1111/ijfs.13045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid whey on physicochemical characteristics of dry‐cured organic pork loins without nitrite

Abstract: The present study deals with the effect of acid whey (AW) on physicochemical properties of non-nitrite organic dry-cured pork loins. The loins were divided into three experimental batches: with the curing mixture (C), with sea salt (S) and with sea salt combined with AW (SW). The evolution of physicochemical properties, colour, fatty acid profile and microbiological quality were assessed at 0, 30 and 90 days of refrigerated storage. Physicochemical parameters of dry-cured organic loins were significantly (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…No change in the content of PUFAs during ripening is surprising, but this was confirmed by low TBARS values which showed minor changes of oxidation occurring in the sausages during the ripening process. The PUFA content obtained for the dry‐fermented sausage was similar to those reported by Stadnik & Stasiak () for organic dry‐cured loins. After ripening, the effect of replacement of curing salt by sea salt and the addition of acid whey was observed.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…No change in the content of PUFAs during ripening is surprising, but this was confirmed by low TBARS values which showed minor changes of oxidation occurring in the sausages during the ripening process. The PUFA content obtained for the dry‐fermented sausage was similar to those reported by Stadnik & Stasiak () for organic dry‐cured loins. After ripening, the effect of replacement of curing salt by sea salt and the addition of acid whey was observed.…”
Section: Resultssupporting
confidence: 93%
“…Our results are not in accordance with the previous studies which have shown that lactic acid bacteria are quite insensitive to nitrite (Hospital et al ., ). This confirms the findings of other authors (Wójciak et al ., ; Stadnik & Stasiak, ). The LAB of organic dry‐fermented sausage after ripening was about 7–8 log CFU g −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors suggested that Lactobacillus strains can increase safety and shelf‐life of food (Franciosi et al ., ; Settanni & Moschetti, ; Russo et al ., ). Moreover, non‐starter LAB from whey could play important role in bioconservation meat product (Wójciak et al ., ,b; Stadnik & Stasiak, ).…”
Section: Resultsmentioning
confidence: 99%